The impact of hand hygiene knowledge on self-efficacy among Spanish nursing students: a cross-sectional study - De Maya-Martínez, Ana; Cauli, Omar; Giménez-Espert, María del Carmen; Buigues, Cristina (Frontiers in Public Health, 2025)
BackgroundHand hygiene (HH) is a good ally to prevent healthcare-associated infections (HAIs). Nevertheless, its incidence continues to concern global bodies such as the World Health Organization (WHO). Nursing student (NS) education will be crucial to reducing HAIs.ObjectiveThe aim of this current study was to establish the level of HH knowledge among Spanish NS in order to identify gaps in their understanding. We also evaluated self-efficacy among NS as a key strategy for infection control (IC).MethodsWe conducted a cross-sectional study of 483 NS in their second, third, or fourth years in the Faculty of Nursing at University of Valencia (Spain). Participants were recruited by convenience sampling; we collected their sociodemographic data, information on their level of knowledge regarding HH using a WHO questionnaire, and their self-efficacy in IC using a questionnaire based on the Health Belief Model, previously validated and showing moderate to high reliability (ICC = 0.63).ResultsThe mean knowledge score was 63.2%, with fourth-year NS achieving significantly higher scores than second-year NS (p < 0.001). The poorest results were those for the WHO “5 Moments for Hand Hygiene” item: only 10.6% identified the need for HH before injections, 19.2% recognized alcohol-based hand rub as more effective than handwashing, and just 21.4% responded correctly regarding HH after patient environment contact. Only 18% correctly identified the main source of pathogens causing HAIs. Self-efficacy scores increased significantly with academic experience (p < 0.001) and correlated positively with HH knowledge.ConclusionIn this single-site study, we found that NS had a moderate knowledge of HH, with those in their third or fourth year scoring better than those in their second year. Self-efficacy in IC might play an important role in preventing HAIs and so it is crucial to enhance the effectiveness of HH among NS to improve clinical competence, student self-confidence, and quality of patient care. These data contribute to a body of knowledge that can help improve the NS training curricula endorsed by international organizations with a view to help prevent HAIs.